Agricultural Crop Residue Based Biomass in India: Potential Assessment, Methodology and Key Issues. (October 2022) - Chauhan, Anurag; Upadhyay, Subho; Saini, Gaurav; Senthilkumar, N.
Graphical abstract: Highlights: Biomass residue yields from different crop is estimated for power generation in Indian perspective. Various available and selection of suitable gasification techniques have been discussed. Different crucial parameters for the usage of agricultural crop residue are elaborated. Maximum capacity of power as 48.35 GWe per year can be generated from crop residue in India. Abstract: Concerns of climate change, depletion of fossil fuels and energy crisis have motivated the world to explore the alternative sources of energy. Renewable sources such as biomass, solar, wind and small hydro are the best alternatives to meet the increasing energy demand. In the present paper, bio energy potential of 12 agricultural crops cultivated in India has been estimated based on gross crop residue (GCR), surplus crop residue (SCR) and crop residue ratio (CRR). Crop statistics and model of GCR and SCR reveal that India produces 1043.24 million tonnes gross crop residue annually, out of which reasonable amount is consumed as cattle feeding, animal bedding, organic fertilizer, fuel for heating and cooking. Additionally, 356.7 MT biomass is available as surplus crop residue on annual basis that can directly be used for power production. The potential assessment of available surplus crop residue has been estimated as 53, 767 MWe per year. Different biomass gasifier technologies are studied and compared based on ash melting temperature, fuel specifications, maximum fuel moisture content, gas lower heating value, and admissible power production. Various key issues (technical, economical, social and environmental) have also been discussed to cover the use of crop residue biomass for power generation.